BIOLOGICAL SPECTRUM OF THE ACTIVITY OF AZHETEROCYCLIC COMPOUNDS (Experimental biology, 2021)
The demand for immunostimulants and immunomodulators in the pharmaceutical market is wide. They are used in the treatment of congenital, acquired immunodeficiency states, in the treatment of cancer patients, in the treatment of patients living in ecologically unfavorable regions of countries, etc. And modern immunopharmacology faces a global challenge in the development of targeted immunostimulants. Thus, the presented spectrum of immunostimulating drugs shows that each group of immunostimulants has a certain spectrum of side effects and synthetic drugs are a more promising group. Therefore, the screening of new promising immunostimulants of targeted synthetics is justified. To study the hemogram of peripheral blood, we used 48 adult female albino laboratory rats, and phenotyping of lymphocytes was carried out by the conventional method of indirect fluorescence using monoclonal antibodies. As a result, the blood leukogram changed towards the development of leukopenic processes. Compound 2 exhibited comparatively low lymphopoiesis-stimulating activity among the compounds studied. Compound 3 showed comparatively high lymphopoiesis-stimulating activity in the series of compounds 1, 2, and 3. The erythropoiesis-stimulating and thrombocytopoiesis-stimulating activity of compounds 1 and 3 was at the level of the reference drug methyluracil.